Eu-doped carbon quantum dot as a selective probe for visualizing and monitoring sulfite in biological systems - Kan, Bo; Li, Li; Hou, Jiaoyu; Liu, Shuyan; Tian, Zhenwei; Sun, Qianchuang (Frontiers in Bioengineering and Biotechnology, 2023)
The detection of SO3 2-in complex environments and its visualization at the cellular level are critical for understanding its role in biological processes. In this study, we developed an Eudoped long-wavelength fluorescent carbon quantum dot (CD2) and investigated the detection mechanism, interference effects and cellular imaging applications of the fluorescent probe CD2.The results show that the addition of SO3 2-induces an electronic rearrangement that restores CD2 to its original structure, leading to a rapid increase in fluorescence intensity. Selectivity experiments showed that CD2 has excellent selectivity to SO3 2-, with minimal interference from common anions. In addition, CD2 shows good biocompatibility for cellular imaging applications, as evidenced by the high cell viability observed in HeLa cells. Using confocal microscopy, we detected a significant enhancement of red fluorescence in HeLa cells after addition of exogenous SO3 2-, demonstrating the potential of CD2 as a probe for monitoring cellular SO3 2-levels. These findings highlight the promise of CD2 as a selective SO3 2-detection probe in complex environments and its utility in cellular imaging studies. Further studies are necessary to fully exploit the potential of CD2 in various biological and biomedical applications.